DESIGNING 2D INTERACTIVE MULTIMEDIA ASSETS FOR TEACHING MAN-MADE FEATURES IN ELEMENTARY SCHOOL - Nugroho, Anggoro Agung (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Learning the subject of Man-made Features in elementary school often faces challenges, such as the presentation of abstract concepts and the lack of visual representation in conventional media. This research addresses this gap by designing a set of engaging and cheerful 2D assets as a technological learning solution. This study aims to design a 2D illustration asset package capable of visualizing various Man-made Features in an appealing and easily comprehensible manner. Employing a Design-Based Research (DBR) methodology, the process involved three stages: analysis, design, and evaluation. The analysis phase identified students' visual needs and style preferences to establish a robust design concept. This concept was then realized in the design phase through sketching and the creation of a visual style guide, including color palettes and typography. The final stage involved the evaluation of the designed assets. The primary output of this research is a comprehensive illustration set, which includes highly detailed 2D assets, a consistent user interface (UI) with a fresh aesthetic, a logotype, and gamification elements such as puzzles. The significance of these assets lies in their potential to capture the interest and imagination of elementary students, thereby significantly enhancing their understanding of the Man-made Features curriculum.